Evaluation of 436 cases of vaginal hysterectomy for benign indications: Experience from a tertiary hospital (Annals of Medical Research, 2023)
Aim: Though vaginal hysterectomy could be a minimally invasive type of hysterectomy, its preference has recently attenuated. We tend to aim to gauge the results of vaginal hysterectomies performed in our clinic for benign indications. Materials and Methods: This retrospective study was conducted on 436 Women who underwent vaginal hysterectomy for benign indications at Kanuni Sultan Suleyman Training and Research Hospital. Between January 01, 2017, and December 31, 2020. Female patients aged between 40 and 85 who underwent vaginal hysterectomy for benign indications was enclosed within the study. The patients with malignancy; or missing records were excluded from the study. Common indications for hysterectomy consisted of pelvic organ prolapse 385 (88.30%) and stress urinary incontinence 22(5.50%). SPSS version  24.0  was used to conduct all data analysisResults: The four hundred thirty-six patients had a mean age of 61.07±10.0 years. The mean parity was 4.40±2.60, and the mean BMI was 31.37±1.74 kg/m2. Eighty-percent of the patients were menopausal, and 19% were of reproductive age. In our study, pelvic organ prolapse (67.88%) and abnormal uterine bleeding (18.73%) were the most common causes of hysterectomy. The major and minor complication rates were 8.02%, and 9.40%, respectively, with an overall rate of 17.42%.Conclusion: Though vaginal hysterectomy could be a minimally invasive sort of hysterectomy; surgeons should remember complications throughout the surgery; recognizing and managing complications is crucial in VAH because it can be fatal.
Keywords: Complications; Pelvic organ prolapse; Vaginal hysterectomy